Validity of Traditional Guidebooks for Character Education in Children Aged 4-6 Years - Corry Restuina; Anita Yus; Daulat Saragi (Randwick International of Education and Linguistics Science Journal, 2023)
Early age is the most important and fundamental initial period in the entire range of growth and development of human life. Children in early age from 4-6 years old which still want to know and explore whatever in around them in a game. They mustn’t study seriously such as reading text book, counting number, and memorizing something else. So, in this study aims to determine the validity of traditional play guidebooks as a character education strategy for children aged 4 6 years. The type of research used in this research is development with the ADDIE model. The data collection technique in this study validation. The result of the study show score of 3.50 for language validation which is in the very good category. Score 3.81 for design validation with every good category and score 3.58 for material validation with very guidebook can be used for learning